"Little Things Make Big Things". A Psycholinguistic Analysis of Immigrants' Life Stories - Altomare Enza Zagaria; Amelia Manuti; Giuseppe Mininni (East European Journal of Psycholinguistics, 2014)
Within the last decades, the global economical revolution which has invested the labor market has prompted calls for a redefinition of traditional human resource management practices. The rapid growth of ethnic diversity in the workplace has turned managers' attention to the management of  difference. Yet, cross cultural management has become a priority for most organizations interested in improving competitiveness and in enhancing their human (multicultural) capital. In view of the above, the present study aimed at investigating the process of cultural integration experienced by a group of 12 immigrants workers employed in different Italian organizations. Moving from an applied psycholinguistics perspective, the study collected  narrative interviews as to understand the impact that the new cultural experience may have had on the sense-making procedures used to integrate and reshape their personal and professional identity. The discursive data were processed through Diatextual Analysis as to catch the psychological and linguistic features binding identities to texts and to contexts of experience.ReferencesBerry, J. W. (1974). Psychological aspects of cultural pluralism: Unity and identityreconsidered. Topics in Cultural Learning, 2, 17–22.Berry, J. W. (1992). Acculturation and adaptation in a new society. InternationalMigration Review, 30, 69–85.Berry, J. W. (1997). Immigration, acculturation, and adaptation. Applied Psychology:An International Review, 46, 5–34.Berry, J. W. (2001). A psychology of immigration. Journal of Social Issues, 57,615–631.Caligiuri, P., (2000). Selecting expatriates for personality characteristics: A moderatingeffect of personality on the relationship between host national contact and cross-culturaladjustment. Management International Review, 40(1), 61–80.Hofstede, G. (1984). Culture’s Consequences: International Differences in WorkRelated Values. Newbury Park, CA: Sage.Hofstede, G. (2001). Culture’s Consequences: Comparing Values, Behaviors,Institutions, and Organizations Across Nations. Thousand Oaks, CA: Sage.Lakey, P., (2003). Acculturation: a review of the literature, InterculturalCommunication Studies, XII-2, 103–118.Larsson, R., & Lubatkin, M., (2001). Achieving Acculturation in Mergers andAcquisitions: An International Case Survey, Human Relations, 54(12), 1573–160.Manuti A. & Mininni G. (2013). Narrating organizational change: an appliedpsycholinguistic perspective on organizational identity. Text & Talk, 33(2), 213–232.Manuti, A., Traversa, R. & Mininni, G. (2012). The dynamics of sense making: adiatextual approach to the intersubjectivity of discourse, Text and Talk, 32(1), 39–61.Mininni G. (2005). Diatexts as a mirror of human complexity. World Futures: TheJournal of General Evolution, 61: 165–173.Mininni, G., Manuti., A., Scardigno,, R., & Rubino, R., (2014). Old roots, newbranches: The shoots of diatextual analysis, Qualitative Research in Psychology, 11, 1–16.Redfield, R., Linton, R., & Herskovits, M.J. (1936) Memorandum for the study ofacculturation. American Anthropologist, 38, 149–152.Richard, O., Barnett, T., Dweyer, S., & Chadwick, K. (2004). Cultural diversity inmanagement, firm Performance, and the moderating role of Entrepreneurial orientationdimensions, Academy of Management Journal, 47(2), 255–26.Rudmin, F., (2003). Critical history of the acculturation psychology of assimilation,separation, integration, and marginalization. Review of General Psychology, 7(1), 3–37.Schwartz, S. H. (1992). Universals in the content and structure of values: Theoreticaladvances and empirical tests in 20 countries. In M. Zanna (Ed.), Advances in Experimental SocialPsychology, 25 (pp. 1–65). Orlando, FL: Academics.Schwartz, S., Montgomery M., & Briones, E., (2006). The role of identity inacculturation among immigrant people: theoretical propositions, empirical questions, and appliedrecommendations. Human Development, 49, 1–30 .Slama-Cazacu T. (1961). Langage et Contexte. The Hague: Mouton.Taras, V., Rowney, J., & Steel, P., (2013). Work-related acculturation: change inindividual work-related cultural values following immigration, The International Journal ofHuman Resource Management, 24(1), 130–151.Templer, K., Tay, C., & Chandrasekar, N., (2006). Motivational cultural intelligence,realistic job preview, realistic living conditions preview, and cross-cultural adjustment. Group &Organization Management, 31(1), 154–173.Verkyuten, M., (2005). Immigration discourses and their impact on multiculturalism: Adiscursive an experimental study, British Journal of Social Psychology, 44: 223–240.
Keywords: acculturation; immigrants; cultural psychology; discourse; diatextual analysis.